Penguatan Manajemen Berbasis Sekolah melalui Inovasi Digital: Kajian Peran Artificial Intelligence - Tarigan, Tasya Natalia; Napitupulu, Irene Paulina; Silalahi, Romanna; Pakpahan, Rahel; Manurung, Artha Angelin; Tarigan, Ifanta Fernando (CV. ITTC INDONESIA, 2026)
This study aims to analyze strategies for strengthening School-Based Management (SBM) through the integration of Artificial Intelligence (AI)-based digital innovations. Amidst the demands of the Society 5.0 era, digital transformation has become a strategic necessity to create adaptive and efficient school governance. The method employed is a library research approach, examining 30 reputable national and international journals published between 2021 and 2026, retrieved from the Google Scholar database. The results indicate that AI integration significantly strengthens SBM across five key dimensions: (1) automation of school administration to reduce manual workloads; (2) strengthening transformational leadership through a symbiotic collaboration model between humans and AI; (3) personalization of student management via adaptive learning systems; (4) revolutionizing evaluation systems through automated assessment and instant feedback; and (5) improving the quality of evidence-based decision-making. Despite challenges such as infrastructure limitations and managerial resistance, this study concludes that enhancing digital literacy and organizational readiness are pivotal to the success of SBM transformation in the future.